PENGEMBANGAN MODUL PEMBELAJARAN PERBAIKAN PERALATAN LISTRIK KELAS XII TITL DI SMK NEGERI 14 MEDAN - Bangun, Angga Karisto; Pangaribuan, Wanapri (Universitas Negeri Medan, 2023)
Abstract This research aims to: (1) Find out how to develop a Class XII Electrical Equipment Repair Learning Module at SMK Negeri 14 Medan. (2) Knowing the response of users of the Class XII Electrical Equipment Repair Learning Module at SMK Negeri 14 Medan. (3) Determine the level of feasibility and effectiveness of the Class XII Electrical Equipment Repair Learning Module at SMK Negeri 14 Medan. This research will be tested involving class This type of research is Research and Development (R & D) with the ADDIE research model. The ADDIE research model includes 5 stages, namely first analysis which includes analysis of product needs, second design namely compiling modules, layouts and module materials, third development namely developing products that have been designed for validation in order to get input from media experts and material experts, fourth implementation namely implementing the product to get responses from users (students) to the modules that have been developed, the fifth evaluation is evaluating the module based on several inputs from experts and user responses. The instruments used in this research were a validation questionnaire and a user response questionnaire. The results of this research are known: (1) This research development produced a product in the form of a learning module for Electrical Equipment Repair Class XII TITL at SMK Negeri 14 Medan. (2) The results of product user (student) responses in the